Torta de mamona é tóxica ao nematoide Meloidogyne incognita também pelos compostos orgânicos voláteis - Pedroso, Luma Alaís (2016)
Although castor cake has shown effect in reducing populations of nematodes, little is known about its mode of action, especially involving the toxicity of their volatile organic compounds (VOCs) to these pathogens. This work aimed to study the direct effect of castor cake in different concentrations mixed with the soil and Meloidogyne incognita (MI) eggs, as well as the separate effect of VOCs on eggs and second stage juveniles (J2) of MI. In plastic cups were placed soil, castor cake and MI eggs. The humidity was adjusted to 60% of field capacity and on the surface of this mixture were digged three microtubes. The cups were sealed and placed in incubator at 28 °C for a period of 10 or 20 days for forming the gas chamber (PFGC). In the first microtube was added 1000 MI eggs, in the second and third were injected with syringe 100 and 600 MI J2, respectively, 48 hours before the end of the incubation periods (10 or 20 days). At the end of 10 and 20 days the plastic cover was removed and were evaluated the percentage hatching of J2 and the number of J2 immobile and dead. At that moment, a tomato seedling was planted in the cup and, after 40 days, were evaluated infectivity and reproduction. The suspension of the third microtube (600 J2) was inoculated on tomato plants and after 40 days were also evaluated infectivity and reproduction. The castor cake in any concentration significantly reduced infectivity and reproduction of eggs mixed with soil in the 10 day period. The VOCs that formed the gas chamber on the surface of the mixture (soil and cake) also caused immobility and death of J2 at any PFGC and all castor cake concentrations, besides reducing the hatching of J2 at any concentration of the castor cake, but greater in the period of 20 days. The infectivity and reproduction of J2 exposed to VOCs were significantly reduced at all concentrations compared to the control, in the period of 10 days. By gas chromatography-mass spectrometry were identified volatile molecules released by the soil mix with castor cake. Five of them showed great intensity and were tested in MI J2. Four molecules (phenol, 4-methylphenol, γ-decalactone and 3-methyl-1H-indole) showed nematicidal activity and LC 50 less than or equal to 66.3 ± 18.0 mg L -1 . Besides the castor cake presents nematicides effects on soil infested with MI it emits toxic VOCs to this pathogen.